Deradicalisation Crime Of Terrorism Actors By Police (Case Study In Police Jurisdiction Of Semarang) - Bagus Gani Setiana; Sri Kusriyah Kusriyah (Jurnal Daulat Hukum, 2019)
The paper titled "Deradicalisation Crime Of Terrorism Actors By Police", aims to identify and analyze the role of the National Police in the process of deradicalization of the criminal terrorism in Indonesia, the benefits of deradicalization, as well as the challenges and solutions faced by the National Police in the implementation of the deradicalization.This study uses the Juridical Sociological Approach, with descriptive analysis models, which use the type and source of primary data that is the result of interviews with police personnel and ex-terrorist, as well as secondary data source that literature on the various sub - laws that exist in Indonesia. Also in this study, the authors also used the descriptive method of analysis. That in the end all results were analyzed by using the theory of Aristotle and theory of Justice usefulness of Jeremy Bentham.Based on the research that has been analyzed, then it was concluded that the role of the National Police in deradicalizing the task is enormous, as evidenced by the reduction in the number of terrorism cases in Indonesia from year to year. In addition, the benefits of deradicalization can reduce the number of perpetrators of terrorism by changing the target ideology. But it is undeniable that the Police still face many obstacles, which in this study the authors provide some solutions to these obstacles.Keywords: Deradicalisation; Ideology; Police; Terrorism.